CHALLENGES IN WRITING ACQUISITION: AN INCLUSIVE APPROACH - Vanusa Ruppel, Tabita; Lucia Martiniak, Vera (Revista Gênero e Interdisciplinaridade, 2024)
The study “Challenges in the acquisition of writing: an inclusive approach” aims to analyze the difficulties faced by students in the literacy process, focusing on writing, and proposing inclusive pedagogical practices. The research, conducted in collaboration with the Nepedhi Research Group, adopts a qualitative methodology, using data collection methods such as direct observations, writing hypotheses and diagnostic evaluations. The authors highlight the importance of didactic planning that meets the diversity of students, promoting activities such as reading, creative writing and family involvement. In addition, the study addresses the negative impact of COVID-19 pandemic on children’s writing skills. The research aims to rethink the pedagogical doing to ensure the inclusion and development of writing capabilities, contributing to the formation of a more accessible and effective educational environment.